Kebijakan Counterterrorism Ronald Reagan dan Relasinya dalam Peristiwa Pembajakan Pesawat Trans World Airlines Flight 847 - Dionisa Bilqis Gusnisar; Eka Rima Oktaviana; Guntur Mahesa; Mita Anggraini; Muhammad Iqbal (FISIP Universitas Tanjungpura, 2022)
This article aims to explain Ronald Reagan’s policy to attempt various counterterrorism actions, such as the formation of Research and Development in technology to minimize opportunities for terrorists to carry out acts of terrorism. In the aftermath of World War II, there were countries that switched from the form of empires to modern states. This happens in countries in the Middle East and causes upheaval from people who disagree. One of the countries that experienced it was Lebanon which wanted to switch to a modern state, but many were not approved by the Syiah community of Lebanon. In addition, government support for Israeli and pro-United States independence also added to the domestic upheaval. Israel's intervention in Lebanon and the capture of the Lebanese Syiah community by Israel, supported by the United States, worsened the situation. In 1985 there was an event that Piracy Hijacking Trans World Airlines flight 847 (TWA flight 847) was allegedly carried out by Hezbollah groups consisting of Lebanese Syiah and was a form of resistance against the United States that supported the Lebanese and Israeli governments. The hijacking also aims to fulfil Lebanese Syiah demands to free the Lebanese Syiah community detained by Israel. For this reason, the United States, during Ronald Reagan's leadership, emerged as a counterterrorism state and opposed all forms of terrorism. This paper uses data collection techniques using literature studies from books, and journals, including data from trusted websites that support the explanations in this paper.